An Efficiency Study in Indonesian Telecommunication Company Using Data Envelopment Analysis DEA - Amin, Kokoh Kabul; Hendrawan, Riko (Journal of Social Research, 2023)
PT. Telekomunikasi Indonesia, Tbk (Telkom), as a state-owned company, has a dual mission, namely as a business company that must be managed professionally, as well as being mandated by the Indonesian government to accelerate the development of information technology, telecommunications, and digital infrastructure to improve the Indonesian economy. Until early 2018, Telkom with Indihome fixed broadband products had reached 3 million customers and a market share of 57.69%. However, that is only 4.50% of the 2019 IBP household penetration target. Telkom is required to increase productivity, especially the number of customers and revenue, while the allocation of available resources is limited and varies in each region. Another condition is the significant reduction in staff due to massive retirements and differences in employee productivity levels in each division. This research aims to determine and compare the efficiency level of 7 Telkom Regional Divisions for the 2016-2018 period using the DEA Data Envelopment Analysis method, with data collection based on the census. The analysis process goes through two stages, namely using the DEA Data Envelopment Analysis method, Constant Return to Scale (CRS/CCR), output-oriented. The next step is to measure the strength of the relationship between each input/output variable on efficiency using Pearson's correlation. The results of the study concluded that Divisions E and B have the highest efficiency values. On the other hand, Division G is the lowest. The variables that have the strongest correlation with the level of efficiency are the number of employees (input), the number of customers (output), and business income (output).